2019
DOI: 10.1108/ijse-12-2018-0643
|View full text |Cite
|
Sign up to set email alerts
|

Public health expenditure and child mortality in Southern Africa

Abstract: Purpose The purpose of this paper is to empirically assess the effect of public health expenditure on child mortality in the Southern African Development Community (SADC) region in comparison to the developing world as a whole and the region of Sub-Saharan Africa (SSA). Design/methodology/approach This study used panel data extracted from the World Development Indicators database for the period 2000–2013 for 98 developing countries including 15 SADC countries. A dynamic panel data model of child mortality wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…The GDP per-capita was found to be positively significant, which indicates that a 1% increase in GDP per-capita leads to about a 2.5% increase in the under-five mortality rate in Malaysia. Almost all the relevant literature reviewed in this study reported either a negative relationship [ 18 , 25 ] or no significance [ 8 , 9 , 11 , 13 ]. Except for Kulkarni [ 15 ], whereby a positive, significant relationship was revealed between GDP per-capita and infant mortality rate in an analysis among BRICS countries (Brazil, Russia, India, China, and South Africa).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GDP per-capita was found to be positively significant, which indicates that a 1% increase in GDP per-capita leads to about a 2.5% increase in the under-five mortality rate in Malaysia. Almost all the relevant literature reviewed in this study reported either a negative relationship [ 18 , 25 ] or no significance [ 8 , 9 , 11 , 13 ]. Except for Kulkarni [ 15 ], whereby a positive, significant relationship was revealed between GDP per-capita and infant mortality rate in an analysis among BRICS countries (Brazil, Russia, India, China, and South Africa).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, in Nigeria [ 8 ], it was found that increases in the urban population decrease infant mortality rates, while per-capita income has no significance. Similarly, public health expenditure was also found to be effective in reducing the infant mortality rate among West African countries [ 11 ] and the under-five mortality rate in developing countries [ 12 , 13 ]. In addition, immunization, female literacy, improved water sources, and good sanitation are among other variables that hold a vital role in reducing child mortality rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the extant literature, some studies (see, for example [ 3 , 10 , 19 , 43 , 61 – 64 , 66 ]) investigated the effects of public health expenditure on infant and child mortality rates in the context of African regions These studies found that public health expenditure significantly reduced infant and child mortality rates in African regions. Conversely, Akinlo and Sulola [ 3 ] revealed that government health expenditure increased infant and child mortality in sub-Saharan Africa due to the high level of corruption of public health expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies (see [ 2 , 3 , 10 , 28 , 33 , 43 , 62 64 , 78 ]) have attempted to investigate the determinants of infant and child mortality. However, unanimous, inclusive, and convincing policy outcomes are not properly perceived, especially for the mentioned African countries (see section- 3.1).…”
Section: Introductionmentioning
confidence: 99%
“…Ironically sub-Sahara Africa, where West Africa is located, has gaps in health financing, infrastructure, and qualified health labor. 12 These problems, coupled with dwindling foreign donations to health care and poor domestic health financing, which is demonstrated in the inability of nations to adhere to the 2001 Abuja declaration, 13 were already impacting health delivery to the general public and severely affecting the continuous treatment of chronic disease patients. The outbreak has worsened the already difficult situation for chronic disease patients.…”
Section: Introductionmentioning
confidence: 99%